1994
DOI: 10.2307/1382235
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profiles of Populations of Cotton Rats in a Continuum of Habitat Types

Abstract: We examined temporal relationships between characteristics of populations creatton rats (Sigmodon hispidus) and vegetative characteristics of habitats following secondary succession of post oak (Quercus ste/lata)-blackjack (Q. rnarilandica) savannas in central Oklahoma. Successional changes in vegetation were induced on manipulated habitats by one of two herbicides (tebuthiuron, triclopyr) applied in 1983 and used in combination with or without annual prescribed burning during 1985 to 1988, Relative population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…P. leucopus and N. floridana were captured most frequently in late-successional areas with high amounts of woody dicots, whereas S. hispidus had the highest numbers in earlysuccessional habitats with greater amounts of monocots. Densities of all rodents were higher in early and late succession and lowest in forest habitats with little herbaceous cover (McMurry et al 1993(McMurry et al , 1994(McMurry et al , 1996. These results correspond to our findings that diversity and abundance were lowest in the cross timbers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…P. leucopus and N. floridana were captured most frequently in late-successional areas with high amounts of woody dicots, whereas S. hispidus had the highest numbers in earlysuccessional habitats with greater amounts of monocots. Densities of all rodents were higher in early and late succession and lowest in forest habitats with little herbaceous cover (McMurry et al 1993(McMurry et al , 1994(McMurry et al , 1996. These results correspond to our findings that diversity and abundance were lowest in the cross timbers.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies at an area adjacent to our study sites found that P. leucopus, S. hispidus, and N. floridana responded to successional changes in habitat (McMurry et al 1993(McMurry et al , 1994(McMurry et al , 1996. P. leucopus and N. floridana were captured most frequently in late-successional areas with high amounts of woody dicots, whereas S. hispidus had the highest numbers in earlysuccessional habitats with greater amounts of monocots.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Selection of young pines in the Mississippi studies was primarily due to relative abundance of small mammals in young pines (Conner 1991, Conner et al 1992. Many young pines in our study area contained little herbaceous vegetation and few small mammals (Golley et al 1965, Schnell 1968, McMurry et al 1994, Masters et al 1998, which may explain why bobcats were farther from young pines.…”
Section: Discussionmentioning
confidence: 83%
“…In a system managed by frequent fire return intervals (≤ 3 years), herbaceous plant communities do not shift to dense hardwood understory communities (Glitzenstein et al 2012). Therefore, these systems contain diverse understory plant communities (Brockway and Lewis 1997), which can produce abundant small mammal populations (Golley et al 1965, Schnell 1968, McMurry et al 1994, Masters et al 1998. We suspect bobcats selected mature pine and mixed pine-hardwoods due to the availability of prey (see also Sasmal et al 2017); however, we lack data on prey availability among the vegetation types on our study area.…”
Section: Discussionmentioning
confidence: 99%